Experimental Study and Finite Element Analysis on the Seismic Performance of Ancient Architectural Kanchuang Frame with Different Impact Parameters Considered - Junhong Huan; Xiaoyi Zhou; Xiaodong Guo; Wei Wang; Donghui Ma; Yue He (BioResources)
To study the seismic performance of ancient timber structures with attached windows and masonry walls,  a low-cycle reciprocating load test was conducted on a 1:2 scaled model of the Kanchuang frame. The frame’s failure modes, hysteretic behavior, skeleton curves, stiffness degradation, and energy dissipation capacity of the frame were obtained. Test results showed that the masonry wall of the structure was the first to crack and fail. The tenons of the wood window pulled out of the mortises gradually while the loading displacement increased. In addition, finite element models of the Chinese traditional Kanchuang frame were established and analyzed. The test results were basically consistent with the finite element analysis results. Based on the finite element models, the influences of impact parameters including friction coefficient, elastic modulus, compressive strength in parallel-to-grain directions, and vertical loads on the seismic performance of the Kanchuang frame were analyzed. The results showed that the ultimate load-bearing capacity, initial stiffness, and energy dissipation capacity of the Kanchuang frame are increased with the increase of friction coefficient, compress strength, and the elastic modulus. The influence of elastic modulus in perpendicular-to-grain directions was minor. The initial stiffness and energy dissipation capacity of the structure increased while the vertical loads increased. However, the ultimate peak loads and stiffness decreased with the increase of the vertical loads.